Magnetic Arthropod Millirobots Fabricated by 3D‐Printed Hydrogels. (19th October 2021) - Sun, Bonan; Jia, Rong; Yang, Hang; Chen, Xi; Tan, Kai; Deng, Qian; Tang, Jingda
Abstract : Magnetically driven small‐scale soft robots are promising for applications in biomedicine, due to their fast, programmable deformation, and remote, untethered actuation to accomplish complicated tasks. Although diverse materials and designs have been proposed for magnetic soft robots with programmable shape transformation, it is still challenging to produce strong actuation by a small magnetic field. Inspired by arthropod species, magnetic soft millirobots with joint structures by 3D printing hydrogels have been developed. The joints can turn the bending deformation into the folding deformation, with the jointed region deforming locally. Different from homogeneous bending deformation, such local deformation allows larger motions of robots and reduces the overall energy consumption at the same time. Through experiments and numerical simulations, it is shown that the magnetic arthropod millirobots are capable of performing multimodal locomotion and programmed shape transformation, such as move, flip, catch, carry, and release. Finally, ex vivo experiments of removing a foreign object from porcine organs (e.g., aorta, stomach, and intestine) are presented to demonstrate the potential surgery application of magnetic arthropod millirobots. Abstract : Magnetic arthropod millirobots have been fabricated by 3D‐printed hydrogels. Inspired by jointed limbs of arthropod species, joint geometry is studied and introduced into the magnetic arthropod millirobots. The six‐armed millirobot demonstrates multimodal locomotion, including move, flip, catch, carry, and release. Foreign body removal is performed in porcine organs ex vivo using the six‐armed millirobots.